Effects of ghrelin on colonic anastomosis following radiotherapy - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2016)
Background: Ghrelin has been reported to have properties such as inducing proliferation, migration and angiogenesis of vascular endothelial cells and has anti-inflammatory effects which may help wound healing in anastomosis following neoadjuvant radiotherapy. Materials and methods: Rats were randomized into 4 groups: control group (1) underwent colonic anastomosis without treatment; ghrelin group (2) which received a single dose of ghrelin following colonic anastomosis; radiation group (3) which recieved a single dose of radiation 5 days before anastomosis; radiation + ghrelin group (4) which received a single dose of radiation 5 days before anastomosis and ghrelin following anastomosis. Anastomotic bursting pressures of the rats which were sacrificed 7 days after surgery were measured. The anastomotic segment was extracted for tissue hydroxyproline, luminol and lucigenin measurements, and histopathological examination as well. Blood samples were obtained for measurement of TNF-alpha and IL-1 beta plasma levels. Results: Bursting pressures of anastomosis and hydroxyproline levels were significantly higher in control and radiation + ghrelin groups than in radiation group. Tissue luminol and lucigenin levels as well as plasma TNF-alpha and IL-1 beta levels were significantly lower in control and radiation + ghrelin groups than in radiation group. Histopathological assessment revealed that administration of ghrelin resulted in regression of inflammation which was severe in radiation group. Conclusion: The adverse effects of radiotherapy on mechanic and histological parameters of anastomosis healing were attenuated by ghrelin therapy by reducing plasma proinflammatory cytokines and tissue reactive oxygen radicals.
Keywords: Ghrelin; radiotherapy; anastomosis; oxidative stress; healing; TRINITROBENZENE SULFONIC-ACID; GROWTH-HORMONE TREATMENT; RECTAL-CANCER; PREOPERATIVE IRRADIATION; RATS; DISEASE; BOWEL